GAMBARAN FAKTOR PENYEBAB PRE EKLAMPSIA/ EKLAMPSIA PADA IBU HAMIL DI PUSKESMAS KALISAT KABUPATEN JEMBER - Nabila Istifadah (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2015)
One of the cause of morbidity, maternal and fetal mortality is preeclampsia [PE] which, according to the WHO range between 0.51% - 38.4%. In the eastern Java at 34.71% of pregnant women die from preeclampsia / eclampsia. In Kalisat health centers are 248 cases of high risk pregnant women and 35 cases with preeclampsia / eclampsia (7.44%), the purpose of this study is to describe the factor in preeclampsia / eclampsia in health center of Kalisat Jember regency. This type of research is descriptive. The populations in this study were 35 pregnant women with the sampling technique used is the total sampling. Data were analyzed using frequency tables using statistical product and service solution (SPSS). The results of this study indicated that the factors cause preeclampsia / eclampsia in health center of Kalisat Jember regency based mostly maternal age <20 or> 35 years 22 (62.9%), had children 1-2 is 22 (62.9%), had a history of hypertension 20 (57.1%), had over weight body is 23 (65.7), not because of a history of diabetes mellitus is 4 (11.4%), and not because of pregnancy gemeli is 1 (2.9%). The conclusion of this study is the trend factor in preeclampsia / eclampsia in health center of Kalisat Jember regency is overweight so it is necessary for balancing input and output of energy / calories